IN VIVO ANTIMALARIAL AND CYTOTOXIC PROPERTIES OF ANNONA SENEGALENSIS EXTRACT - Ajaiyeoba, Edith; Falade, M.; Ogbole, O.; Okpako, L.; Akinboye, Dora (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
The in vivo animal antimalarial and in vitro cytotoxic activities of the methanol extract of Annona senegalensis Pers. (Annonaceae) was investigated in this study. The in vivo antimalarial activity of the methanol extract against Plasmodium berghei was assessed using the 4-day suppressive test procedure. The extract of A. senegalensis had intrinsic antimalarial property that were dose – dependent. At doses of 100mg/kg weight of mice, it produced significant chemosuppression of parasitemia (> 57%) when administered orally. It had the highest activity at 800mg/kg weight of mice (91.1%) compared to Chloroquine disphosphate, the standard reference drug which had a chemosuppression of 96.2%. The in vitro cytotoxicity evaluations were perfomed using A2780 ovarian cancer cells in the drug sensitivity assay. Extract of A. senegalensis exhibited low cytotoxicity with an IC50 of 28.8μg/ml. Preliminary phytochemical screening of the plant extract indicated the presence of alkaloids, saponins, tannins and cardiac glycosides. This finding supports the traditional use of the plant for the treatment of malaria.